Post-activation potentiation (PAP): Effect on target performance in archery - Burcu, B.; Bülent, T. (International Journal of Life science and Pharma Research, 2022)
Post-activation potentiation (PAP) is a physiological phenomenon referring to acute improvement in muscle`s ability to generate strength and thus performance potentially. The purpose of this study was to investigate the effect of PAP on target performance in archery. Thirteen male archery athletes competing in Olympic archery voluntarily participated in this study. Participants` ages, experience in this sport (years), stature, body mass, body-mass index, bent-over row 1 repetition maximum (1RM) 85% were determined in the first session. PAP protocols were applied with a load of 85% of 1RM. Athletes participated in each protocol in a crossover design. The test protocols applied to athletes were as follows; Archery Specific Warm-up Protocol (ASW), fiveminutes rest following PAP protocol prior to the first phase (PAP5), eight-minutes rest following PAP protocol prior to the first phase (PAP8), and lastly eight-minutes rest PAP protocol before both phases (PAP8x2). After each protocol, athletes shoot at targets set at 60 meters away, and each score was recorded. Statistical analyses were conducted using SPSS 20, and statistical significance was set at p<0.05. One-way ANOVA with repeated measures was used for normally distributed data. No statistically significant difference was determined between ASW and PAP protocols, yet better target performance was noted following PAP considering score means. The findings of this study suggest that PAP protocols applied before shooting are effective considering score means even though this effect is not statistically significant. Per this trend, both the positive effects of PAP on performance, particularly on strength, and the need for considering PAP for each athlete individually are suggested not to be overlooked.